Phenotypic and genomic characterization of Bathyarchaeum tardum gen. nov., sp. nov., a cultivated representative of the archaeal class Bathyarchaeia - Khomyakova, Maria A.; Merkel, Alexander Y.; Mamiy, Dana D.; Klyukina, Alexandra A.; Slobodkin, Alexander I. (Frontiers in Microbiology, 2023)
Bathyarchaeia are widespread in various anoxic ecosystems and are considered one of the most abundant microbial groups on Earth. There are only a few reports of laboratory cultivation of Bathyarchaeia, none of the representatives of this class has been isolated in pure culture. Here, we report a sustainable cultivation of the Bathyarchaeia archaeon (strain M17C Ts ) enriched from an anaerobic sediment of a coastal lake. The cells of strain M17C Ts were small non-motile cocci, 0.4-0.7 µm in diameter. The cytoplasmic membrane was surrounded by an S-layer and covered with an outermost electron-dense sheath. Strain M17C Ts is strictly anaerobic mesophile. It grows at 10-45°C (optimum 37°C), at pH 6.0-10.0 (optimum 8.0) and at NaCl concentrations of 0-60 g l −1 (optimum 20 g l −1 ). Growth occurred in the presence of methoxylated aromatic compounds (3,4-dimethoxybenzoate and vanillate) together with complex proteinaceous substrates.Dimethyl sulfoxide and nitrate stimulated growth. Phylogenomic analysis placed strain M17C Ts to BIN-L-1 genus-level lineage from the BA1 family-level lineage and B26-1 order-level lineage (former subgroup-8) within the class Bathyarchaeia. The complete genome of strain M17C Ts had a size of 2.15 Mb with a DNA G + C content of 38.1%. Based on phylogenomic position, phenotypic and genomic properties we propose to assign strain M17C Ts to a new species of a novel genus Bathyarchaeum tardum gen. nov., sp. nov. within the class Bathyarchaeia. This is the first sustainably cultivated representative of Bathyarchaeia. We propose under SeqCode the complete genome sequence of strain M17C Ts (CP122380) as nomenclatural type of Bathyarchaeum tardum, which should be considered as a type for the genus Bathyarchaeum, which is proposed as a type for the family Bathyarchaeaceae, order Bathyarchaeales and of the class Bathyarchaeia.